Pengembangan Ebook Interaktif Taksi (Cerita Fiksi) sebagai Media Keterampilan Apresiasi Sastra - Laili, Yulia Rohmatul; Putriani, Ida; Widiastuti, Sripit (Faculty of Teacher Training and Education, Musamus University, 2021)
Literary appreciation is the skill of understanding, living, and giving opinions on a literary work. Observations of literary appreciation learning in 3 elementary schools showed literary appreciation learning by lecture method, and 66% of children had difficulty appreciating stories. The purpose of this research is to develop an media interactive ebook Taksi (Fiction Story) that deserves to be used in the study of literary appreciation. This type of research is Research and Development (RnD) uses Borg and Gall development models that have been adapted using 7 steps (potential and problems, data collection, product design, design validation, design revision, readability test, product revision). Data analysis using descriptive quantitative. The percentage feasibility of interactive ebook Taksi (1) material and language experts is 86% (2) multimedia and learning media experts by 85%. Teacher readability test results by 88%. Student readability test results by 99%. Thus, media interactive ebook Taksi deserves to be used as a learning medium.